FORMULATION AND EVALUATION OF A CHITOSAN-PVA-GELLAN INSULIN IMPLANT - S., Satish C. (International Journal of Applied Pharmaceutics, 2017)
Objective: The purpose of this study was to ascertain the applicability of degradable materials for fabrication of an insulin release system. Methods: Insulin implants were prepared by using poly (vinyl alcohol) (PVA), gellan and chitosan by solution casting method. The prepared implants were evaluated for swellability, content uniformity, potency and purity of insulin in implants, scanning electron microscopy studies, in vitro release studies, in vitro degradation studies using lysozyme, stability studies and circular dichroism spectroscopy. Results: The swelling degree of the implants was found to be in the range of 1.07-1.56. The diffusion coefficient of water through the implant was found to depend on the calcium chloride (CaCl2) concentration. The diffusion coefficient of insulin through the chitosan-PVA-gellan in the early stages was found to be in the range of 1.99´10-5 cm2/sec to 5.24´10-5 cm2/sec and at later stages in the range of 6.9´10-6 cm2/sec to 1.10´10-5 cm2/sec. The weight of the implants was 48±0.58 mg. The insulin content in the implants was 9.86±0.10 mg. The potency of insulin extracted from the implants was 27.11±0.75 U/mg or 95.12±2.61 % of the control insulin. The in vitro release studies showed that insulin was released completely in a period of 13-19 d depending on the composition of the implant. The increase in CaCl2 retarded the rate of insulin release whereas the increase in PVA content leads to the rapid release of insulin. The device was found to undergo significant weight loss due to enzyme mediated degradation. Conclusion: These studies provide validity for the potential utility of chitosan-PVA-gellan implant systems for the delivery of insulin. The studies also demonstrate that insulin maintained its integrity within the implant system. Implants showed the complete release of insulin in 19 d and the release of insulin from the implants depended on the amount of CaCl2.